Walden : and "On the duty of civil disobedience" - Thoreau, Henry David, 1817-1862. (New York : Holt, Rinehart and Winston, 1964)
Presents "Walden: or, Life in the Woods," American individualist Henry David Thoreau's philosophical chronicle of his life on Massachusetts' Walden Pond from 1845-47; and his famous essay on individual liberty and protest, "On the Duty of Civil Disobedience.".
Walden or, life in the woods -- "On the duty of civil disobedience".
"Revised and updated bibliography."
Cover title: Walden and "Civil disobedience.
Includes bibliographical references.
Adult
Adult.
Notable/Best Books (A.L.A.)
Keywords: Thoreau, Henry David, -- 1817-1862 -- Homes and haunts -- Massachusetts -- Walden Woods; Authors, American -- 19th century -- Biography; Wilderness areas -- Massachusetts -- Walden Woods; Natural history -- Massachusetts -- Walden Woods; Civil disobedience; Solitude; Walden Woods (Mass.) -- Social life and customs; Thoreau, Henry David, -- 1817-1862.; American authors -- Biography; Wilderness areas -- Walden Woods (Mass.); Natural history -- Walden Woods (Mass.); Civil disobedience; Loneliness; Walden Woods (Mass.) -- Social life and customs